A cross-cultural study of persuasive strategies in relationship advice articles in women’s magazines - Reem A. Lulu; Sharifah Nurul Huda Alkaff (Penerbit Universiti Kebangsaan Malaysia, 2019)
Women’s magazines have become the subject of an increasing scholarly exploration as they are widely seen as mirrors of social change in society. They typically cover a variety of topics but one enduring genre is the relationship advice genre. This study presents a cross-cultural analysis of the linguistic constructions of articles in relationship advice columns in women’s magazines. We examine the strategies, which are employed by them to persuade the reader to accept the advice given. We also examine the positioning of the implied reader in these texts by the writers of these articles. Data drawn from six English-language women’s magazines from three contexts which are, the US, Malaysia and the Middle East, was analysed with reference to the linguistic features used as persuasive strategies by the producers of texts, as investigated by several Discourse Analysis (DA) scholars. The findings of the study reveal that in all three contexts, the writers of advice articles in women’s magazines are often seen in a ‘balancing act’ as they set themselves up as experts while at the same time constructing themselves as a friend of the reader. However, we also found evidence of differences in how the reader is positioned as well as the strategies of persuasion used in the different contexts which we believe is attributed to the differences in the cultural norms and values of the respective societies.